Sosialisasi Implementasi ABSS (Asian Business Software Solution) Accounting v.27 di SMAN 4 Padang - Sanda Patrisia Komalasari; Creaktivina Faozi Zai; Reza Fahlevi; Yuliana Firdasari; Hanum Yashthafi Anjani; Silmi Silmi; Fitriyeni Oktavia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Manual accounting systems are no longer possible to use in business processes. This is due to the increasing number of business transactions. Therefore, a computer accounting system needs to be implemented immediately. The implementation and use of computer accounting is not only limited to technical aspects but also requires an effective socialization process to ensure acceptance and proper use by users. Socialization can start with those who study accounting. The dedication of this article is the socialization of how to implement Asian Business Software Solution (ABSS) Accounting by applying it, which is v.27 at SMAN 4 Padang. This service activity explained the basic concepts of accounting computers and identified the benefits obtained from their use so that SMAN 4 Padang students can apply them. Of the 34 students who participated in this service activity, 60.6% said that this activity increased their knowledge and motivation to study, while another 39.4% said it was helpful. According to the participants, this service activity had quite an impact on them.